Effects of Ag presence on phases separation and order-disorder transitions in Cu-xAl-Mn alloys - Santos, C. M. A. [UNESP]; Adorno, A. T. [UNESP]; Stipcich, M.; Cuniberti, A.; Souza, J. S.; Bessa, C. V. X.; Silva, R. A. G. (Elsevier B.V., 2019)
The effects of Ag additions on phases separation and order-disorder transitions in the Cu-7Al-10Mn, Cu-9Al-10Mn and Cu-11Al-10Mn alloys have been studied using electrical resistivity measurements with temperature, differential scanning calorimetry, scanning electron and transmission electron microscopies, X-ray diffractometry and electron diffraction analysis. The results indicated that the decrease in Al content reduces the Cu2AlMn phase amount produced on slow cooling. It was also verified that the variation in Al fraction and Ag addition modify the order-disorder transitions temperatures. A schematic phase diagram showing the shift of phases field with addition of Ag has been proposed.
Keywords: Metals and alloys; Phase transformations; Electrical resistivity measurements